2016
DOI: 10.1364/oe.24.025154
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering by oblate particles near planar interfaces: on the validity of the T-matrix approach

Abstract: We investigate the T-matrix approach for the simulation of light scattering by an oblate particle near a planar interface. Its validity has been in question if the interface intersects the particle's circumscribing sphere, where the spherical wave expansion of the scattered field can diverge. However, the plane wave expansion of the scattered field converges everywhere below the particle, and in particular at the planar interface. We demonstrate that the particle-interface scattering interaction is correctly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…This is always the case for convex particles. The concept extends our recent work for the case of an oblate particle near a planar interface [16].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…This is always the case for convex particles. The concept extends our recent work for the case of an oblate particle near a planar interface [16].…”
Section: Introductionsupporting
confidence: 71%
“…To account for multiple scattering of neighboring particles, the SVWF translation operator can be expressed in a plane wave expansion. In practice, one has to ensure that for a given maximal multipole order of the SWE, the in-plane wavenumber of the PWE is truncated in a regime, where the angular spectrum converges [16]. For low values of the maximal multipole order l max , the accuracy is limited by the multipole truncation error, whereas for large l max , the poor condition number of the linear system becomes prohibitive, compare [16,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the divergence of the spherical wave expansion inside the circumscribing sphere [6], the applicability of the T -matrix method is not obvious for such geometries. Doicu et al [7] have demonstrated numerically that in fact, a surprisingly good accuracy is possible, and in a recent paper [8], we have argued that it is the convergence of the plane wave expansion and not of the spherical wave expansion that ensures a valid treatment of the reflected field from the interface. Thereby, it could be confirmed that the T -matrix method is in general valid also for flat particles on a substrate.…”
Section: Introductionmentioning
confidence: 77%
“…Thereby, it could be confirmed that the T -matrix method is in general valid also for flat particles on a substrate. However, the spectrum of the plane wave expansion converges not uniformly, but only pointwise with increasing multipole order of the scattered field's original T -matrix representation [8]. This has direct implications for the design of accurate numerical implementations.…”
Section: Introductionmentioning
confidence: 99%